The Performance and Sound of Civil Servant Shoesan: An Ethnographic Note - Murid, M. (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the performance of civil servants (ASN) in public service by emphasizing the influence of local cultural values. The research was conducted in North Maluku Province and the Special Region of Yogyakarta using a qualitative approach with ethnographic phenomenology. Data were collected through participant observation, informal interviews with journalists, social activists, and service users, supported by a literature review and documentation. The findings reveal that although civil servants in both regions share similar educational backgrounds and resources, the quality of public services differs significantly. In Yogyakarta, civil servants provide friendly, transparent, and egalitarian services shaped by Javanese cultural values, emphasizing social awareness and equality. Conversely, civil servants in North Maluku demonstrate more hierarchical and distant services, influenced by dola bololo values and myths of royal lineage. Simple cultural symbols, such as the sound of civil servants' shoes or the structure of traditional houses, reflect the bureaucratic work ethos. These findings highlight that the evaluation of public service performance should not rely solely on quantitative indicators but must also consider cultural dimensions embedded in society.